Chloroplast genomes of two extant species of Tertiary relict Cercidiphyllum (Cercidiphyllaceae): comparative genomic and phylogenetic analyses. Issue 1 (2nd January 2019) - Zhu, Shanshan; Yin, Pingping; Yap, Zhaoyan; Qiu, Yingxiong
Abstract: Cercidiphyllum, the only member of Cercidiphyllaceae, contains two extant species: Cercidiphyllum japonicum and Cercidiphyllum magnificum . Here, we reported their complete chloroplast genomes by de novo assembly. The chloroplast genome sizes of C. japonicum and C. magnificum were 159, 871 and 159, 899 bp, respectively. The two chloroplast genomes have 99.7% sequence identity and were highly conserved in GC content (37.9%), gene content (132 genes), and gene order. Phylogenetic analysis of the chloroplast genomes confirmed the monophyly of Cercidiphyllum and recovered Cercidiphyllaceae as a member of the 'woody clade' of Saxifragales.